2016
DOI: 10.2147/nds.s74719
|View full text |Cite
|
Sign up to set email alerts
|

Importance of low carbohydrate diets in diabetes management

Abstract: Dietary strategies are fundamental in the management of diabetes. Historically, strict dietary control with a low carbohydrate diet was the only treatment option. With increasingly effective medications, the importance of dietary change decreased. Recommendations focused on reducing dietary fat to prevent atherosclerotic disease, with decreasing emphasis on the amount and quality of carbohydrate. As the prevalence of obesity and diabetes escalates, attention has returned to the macronutrient composition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 95 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…Hepatic insulin sensitivity also improved significantly upon consumption of the protein + drink in the MIR subgroup, suggesting that the relative increase in dietary protein and maybe the relative decrease in carbohydrate intake, also plays a role in hepatic insulin sensitivity. The lower relative carbohydrate content of subjects’ diets in the protein + group as compared to control (daily about 20 g of carbohydrates less in the protein + group) may have contributed to the reduction in fasting plasma glucose and insulin, adipose tissue insulin resistance, and the increase in systemic insulin sensitivity [ 38 , 39 ]. While we observed these beneficial effects of the protein + drink compared to the control drink in the MIR subgroup, we did not observe them in the no-MIR subgroup, suggesting that these protein + drink effects may be MIR subgroup-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic insulin sensitivity also improved significantly upon consumption of the protein + drink in the MIR subgroup, suggesting that the relative increase in dietary protein and maybe the relative decrease in carbohydrate intake, also plays a role in hepatic insulin sensitivity. The lower relative carbohydrate content of subjects’ diets in the protein + group as compared to control (daily about 20 g of carbohydrates less in the protein + group) may have contributed to the reduction in fasting plasma glucose and insulin, adipose tissue insulin resistance, and the increase in systemic insulin sensitivity [ 38 , 39 ]. While we observed these beneficial effects of the protein + drink compared to the control drink in the MIR subgroup, we did not observe them in the no-MIR subgroup, suggesting that these protein + drink effects may be MIR subgroup-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing carbohydrate intake can reduce sugar levels in the blood and resultant reduced for-insulin needs/medication [55]. Some people may experience side effects such as fatigue, headache, nausea, constipation, bad breath, muscle cramps, or nutrient deficiencies [56]. Moreover, some studies have suggested that very low-carbohydrate diets (<50 grams per day) may increase the risk of diabetic ketoacidosis (DKA), a serious condition that happens when too many ketones (acids) produce in our body due to a lack of insulin [55,56].…”
Section: Examples Of Evidence-based Ethno-dietsmentioning
confidence: 99%
“…Acupuncture is a form of TM that originated in Indian and China more than 2000 years ago. It involves the insertion of fine needles into specific points on the body called acupoints which are believed to correspond to different organs or systems in the body [56]. Acupuncture aims to restore the balance of qi (vital energy) and blood flow in the body thus promoting health and healing.…”
Section: Acupuncturementioning
confidence: 99%
See 1 more Smart Citation